RELIGION IN THE TRIBAL ECO-SYSTEM - Vadakkumchery, Johnson (Journal of Dharma, 1992)
It was the 28th day of field-work in Pandevahi village. I was living among the Madia Gond tribals. They belong to Gadchiroli district of Maharashtra. Early in the morning there was a great commotion; people were moving towards the house of the village panchayat member, Vijja Pandu Pungati. The cause of the commotion was his son, who got married just a month ago. The son and his wife were severely affected with fever and headache. Their sickness turned out to be a grave concern for the whole village.